2022
DOI: 10.7759/cureus.25221
|View full text |Cite
|
Sign up to set email alerts
|

Hand Hygiene Auditing: Is It a Roadway to Improve Adherence to Hand Hygiene Among Hospital Personnel?

Abstract: Background Over the years, there has been an increase in hospital-acquired infections (HAIs) among patients in India. One of the main reasons is a lack of compliance with infection control guidelines, such as hand hygiene. So the present study was conducted to determine the compliance of hand hygiene among healthcare workers in a private tertiary care teaching hospital in South India. Materials and methods The prospective observational study was carried out between April 2017 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Similar results were reported in a study that found that during the pandemic period, HCWs compliance with HH improved as a way of self-protection (25). Considering health personnel, the highest compliance with HH was observed in nurses, as in other studies (21,26). Nurses demonstrated greater adherence to HH guidelines than pediatric residents; however, there were no differences compared to pediatricians.…”
Section: Discussionsupporting
confidence: 86%
“…Similar results were reported in a study that found that during the pandemic period, HCWs compliance with HH improved as a way of self-protection (25). Considering health personnel, the highest compliance with HH was observed in nurses, as in other studies (21,26). Nurses demonstrated greater adherence to HH guidelines than pediatric residents; however, there were no differences compared to pediatricians.…”
Section: Discussionsupporting
confidence: 86%
“…Chong (2021) 60 Mazi (2021) 61 Ganesan (2022) 62 Existing hand hygiene preparations are short-acting and must be reapplied before and after each opportunity. Further testing of new long-acting hand hygiene preparations is needed.…”
Section: Contact Precautions and Patient Isolation Have Been Associatedmentioning
confidence: 99%
“…Deep and unconscious habits drive HH behavior and are, therefore, difficult to change (de Wandel, 2017). Commitment to HH practices can be poor, even with the availability of high-quality infrastructure and resources (Ganesan et al, 2022). Neither knowledge nor reasoning about the impact on patient safety is a predictor of HHC (de Wandel et al, 2010;Huis et al, 2012).…”
Section: Introductionmentioning
confidence: 99%